'Emotion is of the essence. … Number one priority': A nested qualitative study exploring psychosocial adjustment to stroke and aphasia. Issue 3 (7th April 2021) - Moss, Becky; Northcott, Sarah; Behn, Nicholas; Monnelly, Katie; Marshall, Jane; Thomas, Shirley; Simpson, Alan; Goldsmith, Kimberley; McVicker, Sally; Flood, Chris; Hilari, Katerina
Abstract: Background: Stroke and aphasia can have a profound impact on people's lives, and depression is a common, frequently persistent consequence. Social networks also suffer, with poor social support associated with worse recovery. It is essential to support psychosocial well‐being post‐stroke, and examine which factors facilitate successful adjustment to living with aphasia. Aims: In the context of a feasibility randomized controlled trial of peer‐befriending (SUPERB), this qualitative study explores adjustment for people with aphasia in the post‐acute phase of recovery, a phase often neglected in previous research. Methods & Procedures: Semi‐structured interviews were conducted with 20 people with aphasia and 10 significant others, who were purposively sampled from the wider group of 56 people with aphasia and 48 significant others. Interviews took place in participants' homes; they were analysed using framework analysis. Outcomes & Results: Participants with aphasia were 10 women and 10 men; their median (interquartile range—IQR) age was 70 (57.5–77.0) years. Twelve participants had mild aphasia, eight moderate–severe aphasia. Significant others were six women and four men with a median (IQR) age of 70.5 (43–79) years. They identified a range of factors that influenced adjustment to aphasia post‐stroke. Some were personal resources, including mood and emotions; identity/sense of self; attitude and outlook; faith and spirituality; and moving forward. Significant others also talked about the impact of becoming carers. Other factors were external sources of support, including familial and other relationships; doctors, nurses and hospital communication; life on the ward; therapies and therapists; psychological support, stroke groups; and community and socializing. Conclusions & Implications: To promote adjustment in the acute phase, hospital staff should prioritize the humanizing aspects of care provision. In the post‐acute phase, clinicians play an integral role in supporting adjustment and can help by focusing on relationship‐centred care, monitoring mental health, promoting quality improvement across the continuum of care and supporting advocacy. What this paper adds What is already known on the subject: Anxiety and depression are common consequences of stroke, with depression rates high at 33% at 1 year post‐onset. There is evidence that the psychological needs of people with aphasia are even greater than those of the general stroke population. Social support and social networks are also negatively impacted. Few studies have examined adjustment when people are still in hospital or in the early stages of post‐stroke life in the community (< 6 months). Further, many stroke studies exclude people with aphasia. What this paper adds to existing knowledge: Adjustment to living with stroke and aphasia begins in the early stages of recovery. While this partly depends on personal resources, many factors depend on external sources of help and support. These include doctors, nurses and hospital communication, their experience of life on the ward, and their therapists' person‐centred care. What are the potential or actual clinical implications of this work?: Clinicians play an integral role in facilitating people with aphasia to utilize their personal resources and support systems to adjust to life after stroke. They can help by focusing on relationship‐centred care, monitoring mental health, promoting quality improvement across the continuum of care and supporting advocacy.